2015
DOI: 10.1165/rcmb.2014-0342oc
|View full text |Cite
|
Sign up to set email alerts
|

Induction of STAT3-Dependent CXCL5 Expression and Neutrophil Recruitment by Oncostatin-M during Pneumonia

Abstract: Acute bacterial pneumonia is a significant public health concern worldwide. Understanding the signals coordinating lung innate immunity may foster the development of therapeutics that limit tissue damage and promote host defense. We have previously shown that lung messenger RNA expression of the IL-6 family cytokine oncostatin-M (OSM) is significantly elevated in response to bacterial stimuli. However, its physiological significance during pneumonia is unknown. Here we demonstrate that OSM is rapidly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 43 publications
0
42
2
Order By: Relevance
“…Among soluble immune mediators altered by prior experience in the macrophage transcriptomes ( Figure 9, A and B), Cxcl9 was of interest for being the only chemokine increased by experience and Osm for encoding oncostatin M, which enhances lung neutrophil recruitment by stimulating CXCL5 expression in epithelial cells (39,43). Both of these cytokines were measured by ELISA in lung homogenates at early time points of pneumonia in naive and experienced mice, and both were increased at the protein level by 7 hours of infection ( Figure 9F).…”
Section: Resultsmentioning
confidence: 99%
“…Among soluble immune mediators altered by prior experience in the macrophage transcriptomes ( Figure 9, A and B), Cxcl9 was of interest for being the only chemokine increased by experience and Osm for encoding oncostatin M, which enhances lung neutrophil recruitment by stimulating CXCL5 expression in epithelial cells (39,43). Both of these cytokines were measured by ELISA in lung homogenates at early time points of pneumonia in naive and experienced mice, and both were increased at the protein level by 7 hours of infection ( Figure 9F).…”
Section: Resultsmentioning
confidence: 99%
“…Another study using an E. coli pneumonia model demonstrated that a bacterial clearance defect when ablating Onconstatin-M during pneumonia was also dependent on the epithelial expression of Cxcl5 (Traber et al, 2015). These studies together with the present study emphasize the important role of epithelial derived CXCL5-secreting cells in orchestrating PMN recruitment to bacterial infection in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblotting. Whole-liver-tissue protein was extracted as described previously (58). Briefly, liver tissues were isolated and homogenized in extraction buffer with 2.0-mm zirconium oxide beads (catalog number ZROB20; Next Advance) using a Bullet Blender tissue homogenizer.…”
Section: Methodsmentioning
confidence: 99%